Retinal Microvasculature and Conjunctival Vessel Alterations in Patients With Systemic Lupus Erythematosus—An Optical Coherence Tomography Angiography Study - Shi, Wen-Qing; Han, Ting; Liu, Ren; Xia, Qiang; Xu, Tian; Wang, Yan; Cai, Shuang; Luo, Shui-Lin; Shao, Yi; Wu, Rui (Frontiers in Medicine, 2021)
Purpose: To evaluate the conjunctival and fundus retinal vessel density in patients with systemic lupus erythematosus (SLE) with optical coherence tomography angiography (OCTA), and to investigate the relationship between vessel density and clinical indicators. Methods: 12 patients with SLE (24 eyes) and 12 healthy controls (24 eyes) were recruited. OCTA was used to examine the superficial retina layer (SRL) and deep retina layer (DRL) in the macular retina and conjunctival capillary plexus of each eye. We calculated the density of the temporal conjunctival vessels, fundus microvascular (MIR), macrovascular (MAR) and total MIR(TMI) and compared the results in both groups. We used annular partitioning (C1-C6), hemispheric quadrants, and Early Treatment Diabetic Retinopathy Study partitioning (ETDRS) to analyze changes in the retinal vascular density. Correlation analysis was used to investigate the association between blood capillary density and clinical indicators. Results: OCTA results showed significant differences in the conjunctival microvascular density (p<0.001). There was no significant difference in MIR, TMI, and MAR in the superficial layers between the SLE and healthy group (p>0.05). The DRL and DTMI （Deeper TMI）densities were decreased in the macular regions of SLE patients (p< 0.05). In the hemispheric segmentation analysis, the superficial MIR was significantly decreased in the IL (inferior left) region of the SLE patients (p<0.05), and the deep MIR in the IR (inferior right) region was significantly reduced (p< 0.05). In the ETDRS partitioning analysis, the superficial MIR in the inferior, right, and left subdivisions was significantly decreased in the SLE patients (p< 0.05). In the circular segmentation analysis, the deep MIR in the C1 and C3 regions was significantly reduced in SLE patients (p< 0.05), while the superficial MIR density was decreased only in the C3 region (p< 0.05). The conjunctival vascular density was negatively correlated with the STMI (Superficial TMI) (r=-0.5107; p=0.0108) and DTMI (r=-0.9418, p<0.0001). There was no significant correlation between vascular density and SLEDAI-2k (Systemic Lupus Erythematosus Disease Activity Index -2000) (P>0.05). Conclusion: Clinically, patients with SLE and patients suspected of SLE should receive OCTA examination in a comprehensive eye examination to detect changes in ocular microcirculation at an early stage.